Efeito de terapias hipolipemiantes nos lípides e esteróis plasmáticos em pacientes de alto risco com proteína c-reativa elevada - Barbosa, Simone Pinto de Melo [UNIFESP] (2013)
Aims: High-risk subjects with elevated C-reactive protein (CRP) are at high risk for cardiovascular events and frequently require potent statins or combined lipid-lowering therapy to achieve lipid targets and decrease in- flammation. Our study aimed at evaluating the effects of three lipid-modifying therapies on LDL-cholesterol, CRP levels and markers of cholesterol absorption and synthesis. Main methods: A prospective intervention study was performed in high cardiovascular risk individuals receiving atorvastatin 10 mg daily for four weeks. Those with CRP ? 2.0 mg/L were randomized to another four-week treatment period with atorvastatin 40 mg, ezetimibe 10 mg or the combination of atorvastatin 40 mg / ezetimibe 10 mg. Lipids, markers of cholesterol absorption (campesterol and ?-sitosterol), and synthesis (desmosterol), as well as CRP were quantified at baseline and end of study. Key findings: One hundred and twenty two individuals were included. Atorvastatin alone or combined with ezetimibe reduced both LDL-cholesterol and CRP (P b 0.002 vs. baseline; Wilcoxon); ezetimibe did not modify CRP. Ezetimibe-based therapies reduced absorption markers and their ratios to cholesterol (P b 0.0001 vs. baseline, for all; Wilcoxon), whereas atorvastatin alone increased campesterol/cholesterol and ?-sitosterol/ cholesterol ratios (P b 0.05 vs. baseline; Wilcoxon). In addition, ezetimibe also increased desmosterol and desmosterol/cholesterol ratio (P b 0.0001 vs. baseline; Wilcoxon). Significance: These results contribute to understanding the link between cellular cholesterol homeostasis, in- flammation and lipid-modifying therapies. Our findings highlight the broader benefit of combined therapy with a potent statin and ezetimibe decreasing inflammation, and preventing increase in cholesterol biosynthesis, an effect not observed with ezetimibe alone.